Evaluation of primary health care nurses’ knowledge and neonatal screening performance for phenylketonuria in Alexandria - Esraa Mohammed Abd El-Samie Ismail; Wafaa Mohamed Elarousy; Shaymaa Saeed Mohamed Badawe; Rasha Mohamed Abohadida (BMC Nursing)
Abstract Introduction Nurses play a crucial role in the primary prevention of phenylketonuria (PKU) within national screening programs for newborns. This is achieved through consult with the child’s provider promptly to arrange a PKU test, accurate collection of blood samples at maternal and child health centers, enable early detection of potential cases. Aim This study aimed to assess the level of primary health care nurses’ knowledge and neonatal screening performance for phenylketonuria in Alexandria Methods A descriptive research design was used. The study included all nurses (50 nurses) who are responsible for obtaining newborn screening test from 5 primary health care centers in Alexandria. Two tools were used to collect the necessary data: nurses’ knowledge regarding phenylketonuria disease assessment sheet and nurses’ performance about newborn screening for phenylketonuria observational checklist. Results It was found that the mean age of participant was 42.94 ± 5.0 and 52% of them had completed their technical level of education and the means years of experience was 17.64 ± 4.84. The total mean score of nurses’ knowledge regarding phenylketonuria screening was 16.24 ± 1.99 with the mean percent score of 72.72 ± 8.27. It was also found the total score of nurses’ screening performance was 11.0 ± 0.97 with the mean percent score of 64.71 ± 5.70. A significant positive correlation was found between nurses’ knowledge and their screening performance with P = < 0.001. Conclusion It was concluded that majority of participant nurses had correct knowledge in neonatal screening and many aspects of phenylketonuria disease. However, they still needed support in steps related to infection control.